Force-dependent allostery of the α-catenin actin-binding domain controls adherens junction dynamics and functions. Issue 1 (December 2018) - Ishiyama, Noboru; Sarpal, Ritu; Wood, Megan; Barrick, Samantha; Nishikawa, Tadateru; Hayashi, Hanako; Kobb, Anna; Flozak, Annette; Yemelyanov, Alex; Fernandez-Gonzalez, Rodrigo; Yonemura, Shigenobu; Leckband, Deborah; et al.
Abstract α-catenin is a key mechanosensor that forms force-dependent interactions with F-actin, thereby coupling the cadherin-catenin complex to the actin cytoskeleton at adherens junctions (AJs). However, the molecular mechanisms by which α-catenin engages F-actin under tension remained elusive. Here we show that the α1-helix of the α-catenin actin-binding domain (αcat-ABD) is a mechanosensing motif that regulates tension-dependent F-actin binding and bundling. αcat-ABD containing an α1-helix-unfolding mutation (H1) shows enhanced binding to F-actin in vitro. Although full-length α-catenin-H1 can generate epithelial monolayers that resist mechanical disruption, it fails to support normal AJ regulation in vivo. Structural and simulation analyses suggest that α1-helix allosterically controls the actin-binding residue V796 dynamics. Crystal structures of αcat-ABD-H1 homodimer suggest that α-catenin can facilitate actin bundling while it remains bound to E-cadherin. We propose that force-dependent allosteric regulation of αcat-ABD promotes dynamic interactions with F-actin involved in actin bundling, cadherin clustering, and AJ remodeling during tissue morphogenesis. Cell-cell adhesion mediated by catenin-cadherin complexes plays a critical role in translating the mechanical forces into physiological responses. Here the authors define a mechanism of force-dependent cadherin-actin linkage dynamically regulated through the actin-binding domain of α-catenin.